Family Planning - Amarin, Zouhair O. (IntechOpen, 2018)
Women with unmet need for family planning are those who are fecund but are not using any method of contraception, not wanting any more children, or wanting to delay the next pregnancy. This notion points to the gap between women?s reproductive intentions and their contraceptive behavior. The need for contraception remains too high. This circumstance is made worse by both a growing population and a shortage of family planning services. It is important that family planning is widely available and easily accessible. This book is intended as an aid to substance that all health workers interested in becoming more effective practitioners will consult on many occasions during their clinical practice. It provides views that the readers can test their experiences against. It presents sound and clear advice on some of the most practical guidance applicable to family planning.